An engineered interleukin‐11 decoy cytokine inhibits receptor signaling and proliferation in lung adenocarcinoma - Brianna J. McIntosh; Griffin G. Hartmann; Sean A. Yamada‐Hunter; Phillip Liu; Camille F. Williams; Julien Sage; Jennifer R. Cochran (Wiley, 2023)
Abstract The cytokine interleukin (IL)‐11 has been shown to play a role in promoting fibrosis and cancer, including lung adenocarcinoma, garnering interest as an attractive target for therapeutic intervention. We used combinatorial methods to engineer an IL‐11 variant that binds with higher affinity to the IL‐11 receptor and stimulates enhanced receptor‐mediated cell signaling. Introduction of two additional point mutations ablates IL‐11 ligand/receptor association with the gp130 coreceptor signaling complex, resulting in a high‐affinity receptor antagonist. Unlike wild‐type IL‐11, this engineered variant potently blocks IL‐11‐mediated cell signaling and slows tumor growth in a mouse model of lung cancer. Our approach highlights a strategy where native ligands can be engineered and exploited to create potent receptor antagonists.